Dynamics in hard condensed matter probed by X-ray photon correlation spectroscopy: Present and beyond. Issue 5 (October 2018) - Zhang (张庆腾), Qingteng; Dufresne, Eric M.; Sandy, Alec R.
Highlights: X-ray photon correlation spectroscopy measures low energy fluctuations in materials. XPCS using area detectors provides length-scale sensitivity to fluctuations. XPCS has provided insight into continuous, evolving and abrupt dynamics in materials. Emerging x-ray sources will measure far faster fluctuations and enable in situ work. Abstract: Insight into the spatial ordering and dynamics of structural heterogeneity in materials is at the heart of understanding their structure and function. X-ray photon correlation spectroscopy (XPCS) measures the dynamic structure factor S ( Q, t ) providing information on the spontaneous low-energy dynamics intrinsic to many materials. Combined with in situ and in operando capabilities, XPCS provides unique insight into a variety of scientific areas, including phase separation in binary alloys, aging in metallic glasses, surface dynamics during growth, domain wall dynamics in ferroic complex oxides and charge and spin density wave motion in quantum materials. This review summarizes some recent XPCS work in these areas and discusses scientific opportunities that will be made possible with the many-fold increase in coherent flux provided by the world-wide construction and commissioning of X-ray sources based on multi-bend achromat (MBA) storage ring (SR) lattices and high repetition rate free electron lasers (FELs).